Systemic therapy for colorectal cancer - Štabuc Borut (Archive of Oncology, 2003)
Colorectal cancer alone accounts for around 200,000 deaths in Europe and represents a significant health problem. Although about fifty percent of patients are cured by surgery alone, the other half will eventually die due to metastatic disease, which includes approximately 25% of patients who have evidence of metastases at the time of diagnosis. Surgical resection of the primary tumor and regional lymph nodes is the only curative therapy for colorectal cancer. However, adjuvant chemotherapy in stage III for colon cancer following curative resection has been shown to reduce the risk of recurrence by 19-40% and of death by 16-33%. Today, 5-fluoroUracil and Leucovorin given for six months may represent the best adjuvant treatment available The contribution of levamisole to adjuvant treatment seems to be marginal, if any. The benefit of adjuvant chemotherapy for the patients with Dukes B colon cancer is less clear. A meta-analysis of 1,381 patients with advanced colorectal cancer showed a significant increase in response rate with the bolus 5-fluoroUracil and Leucovorin versus 5-fluoroUracil alone but no significant difference in median survival. Continuous infusion allows higher doses of 5-FU than rapid bolus infusion and improves response rate survival and time to progression. Oral fluoropyrimidines (capecitabine and Uracil/Tegafur [UFT]) are as active as intravenous fluoropyrimidines. Compared to intravenous 5FU, oral fluoropyrimidines have safety advantages clinical benefits, and are more convenient for patients. Phase III randomized clinical trials in patients with metastatic colorectal cancer demonstrate the significant superiority of combining irinotecan with 5-fluoroUracil and Leucovorin or oxaliplatin with 5-fluoroUracil and Leucovorin over the same 5-fluoroUracil and Leucovorin alone. Several phase II studies have shown that the combination of the oral fluoropyrimidines plus irinotecan or oxaliplatin is very active in metastatic colorectal cancer. Trials with agents acting on novel targets in colorectal cancer are progressing rapidly, including doxifluridine, new inhibitors of thymidylate synthase (ZD9331), oral camptothecins (Rubitecan), multitarget antifolate antimetabolite (Premetrexet), inhibitors of epidermal growth factor receptor (Cetuximab), COX-2 inhibitors (celecoxib) and farnesyltransferaze inhibitors (Zarnestra). However, a few randomized trials failed to show a survival advantage compared with placebo in patients with advanced refractory colorectal cancer.